Multistatic dual-channel detection of drones: effects of PNT errors - Griffin, Benjamin; Balleri, Alessio; Catherall, Aled (Institute of Electrical and Electronics Engineers (IEEE), 2023)
A radar network solution to detect drones is presented that consists of low-cost low-size dual-channel moving receivers, which can be deployed on UASs and operate within the coverage of an existing cooperative or non-cooperative monostatic staring radar. The receivers exploit the use of a dual-channel design and therefore use a reference and a surveillance channel to operate coherently without the requirement of a shared synchronisation reference signal between the network nodes, which is one of the key limitations of other traditional multistatic radar network solutions. Drone detection and parameter estimation is achieved by fusing the information collected at the network receivers and rely on accurate Position, Navigation and Timing (PNT) information. In this paper, we investigate the effects of PNT errors on estimation performance for such a radar network.
Keywords: PNT; Data Fusion; Drone Detection; Multistatic; Radar